PENINGKATAN DISIPLIN ANAK USIA 5-6 TAHUN MELALUI METODE PEMBIASAAN - Nurfitri Sahidun (Institut Agama Islam Negeri Metro, 2022)
The aims of this research are to describe the process of implementation by the habituation method activities and to analyze the increasing of children’s disciplines. Respondents of the research involved of 12 children 5-6 years old at TK Lestari, Lola Kecamatan Oba Tengah. The method of this research consists: (a) plan, (b) action and observation, (c) reflection. The score of data from children disciplines were analyzed by using quantitative and qualitative approach. The results shows that children could improve their discipline, they are like time discipline, discipline in learning, discipline in manners. Quantitative data shows that the children discipline cycles have increased. Based on the data results shows in the end of the first cycle, it shows that children discipline has increased about 10.37%, when pretest children discipline has significantly 41,33 or 46,96%, therefore in the first cycle be 46 or 57,33%. The mean score in second cycle has significantly 64,47 or 79,92.